Democratically consolidated, externally threatened, and NATO aligned: finding unexpected deficiencies in civilian control. Issue 6 (18th August 2019) - Pion-Berlin, David; Acácio, Igor; Ivey, Andrew
ABSTRACT: It has long been presumed in the literature that consolidated democracies that face serious external threats or are NATO-aligned should feature strong, civilian control institutions and personnel. This study of Israel, India, Taiwan, Spain and Poland reveals otherwise. Utilizing biographical data compiled by the authors, we researched civilian personnel within each country's defence ministry – the organizational hub of civil-military relations. Rather than finding evidence of strong civilian control, what we found instead were ministries with serious deficiencies: they did not have effective power; they failed to engage in defence planning or provide strategic guidance to the armed forces; they were led by military personnel and staffed by civilian employees not properly qualified to handle defence affairs. To explain these discrepancies, we argue that long-standing deficits in civilian expertise spur the delegation of ministerial defence positions to more knowledgeable officers. Comparisons are made with benchmark states that have achieved civilian ministerial control.